2011
DOI: 10.1111/j.1551-2916.2011.04989.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Evolution of Calcium Silicate Hydrate (C–S–H) Structures by TotalX‐Ray Scattering

Abstract: High‐energy X‐ray diffraction was employed to study the structural characteristics of a set of C–S–H samples with 0.6 ≤ C/S ≤ 1.75. It has been observed that Si is tetrahedrally coordinated to O for all samples irrespective of chemical composition and the Ca–O coordination number gradually decreases from ~7 to ~6 with increasing C/S ratio. This suggests that the C–S–H structure evolves from a tobermorite‐like structure into a jennite‐like structure as a function of increasing C/S ratio as the interlayer space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 39 publications
(97 reference statements)
9
66
0
1
Order By: Relevance
“…The intensities of G ( r ) in all PDF were rescaled based on the peak intensity of Ca 1 –Si 1 in the PDF of C 3 S paste. In PDFs of cementitious phases, the correlations at ~1.6 Å are related to the average Si 1 –O 1 bond in tetrahedrally coordinated SiO 2 as previously found in synthetic C–S–H and tobermorite . Soyer‐Uzen et al .…”
Section: Resultssupporting
confidence: 57%
“…The intensities of G ( r ) in all PDF were rescaled based on the peak intensity of Ca 1 –Si 1 in the PDF of C 3 S paste. In PDFs of cementitious phases, the correlations at ~1.6 Å are related to the average Si 1 –O 1 bond in tetrahedrally coordinated SiO 2 as previously found in synthetic C–S–H and tobermorite . Soyer‐Uzen et al .…”
Section: Resultssupporting
confidence: 57%
“…In a study to quantify the order and disorder of the molecular structure, Bauchy et al [149] showed that while C-S-H retains some signatures of a tobermoritelike layered structure, hydrated species are completely amorphous. Their modeling captured the main features of pair distribution function results [150] of synthetic C-S-H.…”
Section: Atomistic Modelingmentioning
confidence: 99%
“…In order to shed light and open questions in the chemistry and local atomic structure of C-S-H gels, neutron and synchrotron total scattering data analyzed by PDF methodology have been used, and these studies have been reviewed [25,26]. Here, we distinguish the PDF studies on synthetic C-S-H gels [13,[27][28][29] from those carried out for C-S-H gels formed from the hydration of alite [29][30][31], as the local atomic arrangements could be quite different. These investigations have revealed that the C-S-H gel from alite hydration presents a nanocrystalline nature with atomic ordering up to approximately 40 Å [29,31].…”
Section: X-ray Pair Distribution Function Analysismentioning
confidence: 99%